Suppose that α < x < β is the solution to the following inequality: ( 3 1 ) x 2 + 1 > ( 9 1 ) x + 2 . Then what is the value of β − α ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
the answer is wrong ! the solution to this equation would be : x belongs to (- infinity to -1) U ( 3 to +infinity)
Remember not to assume that the inequality sign will the same "direction"
You did wrong at 2(x+2) part... I did the same mistake and got that answer.
x=(1,3) or {x/1<x<3}
Your answer is wrong. 4 is the correct answer
Problem Loading...
Note Loading...
Set Loading...
( 3 1 ) x 2 + 1 > ( 9 1 ) x + 2 ⇔ ( 3 − 1 ) x 2 + 1 > ( 3 − 2 ) x + 2 ⇔ ( 3 ) − x 2 − 1 > ( 3 ) − 2 x − 4 ⇔ − x 2 − 1 > − 2 x − 4 ⇔ − x 2 + 2 x + 3 > 0 ⇔ x 2 − 2 x − 3 < 0 ⇔ − 1 < x < 3 → β − α = 3 − ( − 1 ) = 4